Pengaruh Literasi Keuangan Syariah dan Religiusitas terhadap Minat Menabung di Kecamatan Palas - Fina Mawadah; Finny Ligery; Agus Setiawan (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
The study aims to determine the influence of Islamic financial literacy and religiosity on interest in saving in Islamic banks. The low level of Islamic financial literacy in the community, especially among madrasah teachers, is still the main obstacle in increasing their participation in the Islamic banking system. Religiosity is also considered an important factor that influences interest in saving in Islamic banks, given Islamic teachings that prohibit the practice of usury and encourage financial management in accordance with sharia principles. The research method uses quantitative analysis with an explanatory approach. The sampling technique is purposive sampling of 55 Madrasah teachers in Palas District. The data was processed using multiple linear regression tests with the help of the SPSS application. The results of the study show that sharia financial literacy and religiosity partially and simultaneously have a positive and significant influence on saving interest. Islamic financial literacy and religiosity are highly prioritized for customers in fostering interest in saving at Islamic banks.